Effects of the peripheral CB1 receptor antagonist JD5037 in mono— and polytherapy with the AMPK activator metformin in a monocrotaline-induced rat model of pulmonary hypertension - Remiszewski, Patryk; Pędzińska-Betiuk, Anna; Mińczuk, Krzysztof; Schlicker, Eberhard; Klimek, Justyna; Dzięcioł, Janusz; Malinowska, Barbara (Frontiers in Pharmacology, 2022)
Pulmonary hypertension (PH) is a disease leading to increased pressure in the pulmonary artery and right heart failure. The adenosine monophosphate-activated protein kinase (AMPK) activator, metformin, has a protective effect against PH. CB1 receptor blockade reduces the number of pathological alterations in experimental lung fibrosis. The current study evaluates the effect of the peripheral cannabinoid CB1 receptor antagonist JD5037 in mono- and polytherapy with metformin in rat monocrotaline-induced mild PH. Animals received metformin (100 mg/kg), JD5037 (3 mg/kg), or a combination of both once daily for 21 days. Monocrotaline (60 mg/kg) increased right ventricular (RV) systolic pressure (RVSP), led to RV and lung hypertrophy and remodeling, and decreased oxygen saturation. Metformin partially restored the monocrotaline-induced effects, i.e. decreased RVSP, increased oxygen saturation, and counteracted cardiac fibrotic, hypertrophic, and inflammatory changes. JD5037 modified parameters related to inflammation and/or fibrosis. Only polytherapy with metformin and JD5037 improved Fulton’s index and coronary artery hypertrophy and tended to be more effective than monotherapy against alterations in RVSP, oxygen saturation and coronary artery tunica media vacuolization. In conclusion, monotherapy with JD5037 does not markedly influence the PH-related changes. However, polytherapy with metformin tends to be more efficient than any of these compounds alone.